2022
DOI: 10.3389/fmed.2022.797104
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of the csy1 Gene in the Antimicrobial Resistance of Acinetobacter baumannii

Abstract: Acinetobacter baumannii is an important, opportunistic nosocomial pathogen that causes a variety of nosocomial infections, and whose drug resistance rate has increased in recent years. The CRISPR-Cas system exists in several bacteria, providing adaptive immunity to foreign nucleic acid invasion. This study explores whether CRISPR-Cas is related to drug resistance. Antibiotics were used to treat strains ATCC19606 and AB43, and the expression of CRISPR-related genes was found to be changed. The Csy proteins (Csy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Many recent studies have shown that the CRISPR-Cas system is closely related to bacterial drug resistance ( 25 , 52 , 53 ). Our previous study observed cas gene expression changes in csy1 single knockout strains under antibiotic stress ( 27 ). However, how the CRISPR-Cas systems regulate antibiotic resistance in A. baumannii remains unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many recent studies have shown that the CRISPR-Cas system is closely related to bacterial drug resistance ( 25 , 52 , 53 ). Our previous study observed cas gene expression changes in csy1 single knockout strains under antibiotic stress ( 27 ). However, how the CRISPR-Cas systems regulate antibiotic resistance in A. baumannii remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…For example, recent studies have shown that A. baumannii uses the I-Fb CRISPR-Cas system to stop the spread of antibiotic resistance genes ( 26 ). Our recent research also demonstrated that the I-Fb CRISPR-Cas-related gene Csy1 in AB43 was upregulated when treated with most antibiotics and only downregulated when treated with doxycycline and kanamycin as an antibiotic pressure ( 27 ). However, it is unclear why this phenomenon occurs and its specific mechanism.…”
Section: Introductionmentioning
confidence: 91%
“…Li’s research revealed that the CRISPR-Cas system of Klebsiella pneumoniae could interfere with the acquisition of exogenous plasmids or phages carrying antibiotic-resistant genes and maintain the sensitivity of strains to antibiotics [ 43 ]. Although our published study shows that A. baumannii AB43 was sensitive to most of the antibiotics, including gentamicin, doxycycline, minocycline, imipenem, kanamycin, ciprofloxacin, ceftriaxone, tigecycline, erythromycin, polymyxin B, colistin, and rifampin [ 9 ], the genome contains a variety of antibiotic resistance-associated genes. The number of antibiotic resistance genes in AB43 was not much lower than the “No CRISPR/No Cas” A. baumannii strain in the research of Tyumentseva [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AB43 strain was used to investigate the relationship between the CRISPR-Cas system and drug resistance. Our published study showed that the csy1 -deleted mutant strain of AB43 was resistant to all of the tested antibiotics except Polymyxin B and colistin, and the wild type AB43 was sensitive to all of the antibiotics we tested, which indicated that the CRISPR-Cas system may be related to drug resistance [ 9 ]. Csy1, Cas proteins, and CRISPR RNA can form the Csy protein, and studies have shown that the Csy proteins strengthen target recognition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strain ATCC19606 is one of the best-characterized strains of A. baumannii , which is widely used to study antimicrobial resistance and other stress [ 14 , 15 , 16 ]. It is resistant to sulfonamide but susceptible to a variety of other antibiotics, including β-lactams, aminoglycosides, quinolones, tetracyclines, and colistin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%